Differences in the Cognitive Processes of Autism Spectrum Disorder Students in Understanding Mathematical Problems Based on the Level of Intelligence - Fauziyah, N; Budayasa, I K; Juniati, D (International Journal of Psychosocial Rehabilitation, 2020)
The porpose of this study is to determine differences in the cognitive processes of autism spectrum disorder (ASD) students in understanding mathematical problems based on different levels of intelligence. The subjects of this study consisted of 3 ASD high school students who had high, medium and low intelligence respectively. Data obtained through task-based interviews using triangulation. ASD subjects with a high intelligence level (ASDH) received information by reading the problem softly, applying voice pressure to certain words, interspersed with laughing and smiling to themselves, repeating certain words and muttering to say an unclear sentence. Whereas ASD subject with a medium intelligence level (ASDM) received information by reading the problem out loud with a rather rapid intonation of voice, without any eye contact with blank eyes. Whereas ASD subject with a low intelligence level (ASDL) received information by reading the problem rather loudly and reading piecemeal sentences. ASDH subject can store information and call back in three forms of visual representation, images, verbal and symbols. Information recalled by ASDM subject in two forms of visual representation, images and verbal. Information recalled by ASDL subject is only in one form of visual representation, in the form of images. ASDH subjects were able to understand well the meaning of the symbols that exist in the problem, while ASDM and ASDL subjects were not able to understand it. ASDH and ASDM subjects can understand well the adequacy of information in the problem, while ASDL subjects are unable to understand it. ASDH subjects were able to reduce information in the questions, while ASDM and ASDL subjects were not able. ASDH and ASDM subjects were able to understand well the patterns of the images in the problem while ASDL subjects were not able to understand them.